1995
DOI: 10.1002/arch.940280102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of KK‐42 on growth, development, molting, and metamorphosis of the european corn borer, Ostrinia nubilalis (Hübner)

Abstract: (1 -benzyl-5-I(E)-2,6-dimethyl-l ,S-heptadienyll imidazole), administered by feeding, delayed the growth and development ot nondiapause-bound and diapause-bound Ostrinia nubilaiis larvae and increased the length of the instar. At doses of 80-240 ppm, 62-1 00% ot nondiapause-bound fourth instars precociously pupated or remained as fourth instars, while 52-100% of diapausebound fourth instars did not molt to the fifth instar. Injection of these nondiapause-and diapause-bound KK-42-fed fourth instars with ecdyson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These data have validated the reported antiecdysteroid activity of other anti-JH compounds in some insects. The imidazole compound KK-42 was found to delay/inhibit the ecdysteroid production in O. nubilalis and S. gregaria [110,111]. Another imidazole SDIII had been reported to exert strong anti-JH and anti-ecdysteroid actions on B. mori [112].…”
Section: Suspended Developmentmentioning
confidence: 99%
“…These data have validated the reported antiecdysteroid activity of other anti-JH compounds in some insects. The imidazole compound KK-42 was found to delay/inhibit the ecdysteroid production in O. nubilalis and S. gregaria [110,111]. Another imidazole SDIII had been reported to exert strong anti-JH and anti-ecdysteroid actions on B. mori [112].…”
Section: Suspended Developmentmentioning
confidence: 99%
“…The antiecdysteroidal activity of KK-42 has been observed in Bombyx mori (Kadono-Okuda et al, 1987b) and the European corn borer, Ostrinia nubilalis (Gelman et al, 1995). The effect was reversed on feeding the treated insects with ecdysone, suggesting a delay/inhibition of ecdysteroid production.…”
Section: Discussionmentioning
confidence: 96%
“…In Manduca sexta, it has been demonstrated that a threshold head capsule size exists for metamorphosis (Nijhout, 1975). Recently it has been reported that when KK-42 is applied to third or fourth instar larvae of the European corn borer, Ostrinia nubilalis, a combination of reduced JH levels, inhibited ecdysteroid synthesis, and the resulting increase in weight gain is responsible for precocious metamorphosis (Gelman et al, 1995).…”
Section: Discussionmentioning
confidence: 99%